GmPIN-dependent polar auxin transport is involved in soybean nodule development - Gao, Zhen; Chen, Zhiwei; Cui, Yuanyuan; Ke, Meiyu; Xu, Huifang; Xu, Qinzhen; Chen, Jiaomei; Li, Yang; Huang, Laimei; Zhao, Hong; Huang, Dingquan; Mai, Siyuan; et al. (The Plant cell, 2021)
To overcome nitrogen deficiency, legume roots establish symbiotic interactions with nitrogen-fixing rhizobia that are fostered in specialized organs (nodules). Similar to other organs, nodule formation is determined by a local maximum of the phytohormone auxin at the primordium site. However, how auxin regulates nodule development remains poorly understood. Here, we found that in soybean, (Glycine max), dynamic auxin transport driven by PIN-FORMED (PIN) transporter GmPIN1 is involved in nodule primordium formation. GmPIN1 was specifically expressed in nodule primordium cells and GmPIN1 was polarly localized in these cells. Two nodulation regulators, (iso)flavonoids trigger expanded distribution of GmPIN1b to root cortical cells, and cytokinin rearranges GmPIN1b polarity. Gmpin1abc triple mutants generated with CRISPR-Cas9 showed the impaired establishment of auxin maxima in nodule meristems and aberrant divisions in the nodule primordium cells. Moreover, overexpression of GmPIN1 suppressed nodule primordium initiation. GmPIN9d, an ortholog of Arabidopsis thaliana PIN2, acts together with GmPIN1 later in nodule development to acropetally transport auxin in vascular bundles, fine-tuning the auxin supply for nodule enlargement. Our findings reveal how PIN-dependent auxin transport modulates different aspects of soybean nodule development and suggest that the establishment of auxin gradient is a prerequisite for the proper interaction between legumes and rhizobia.
Keywords: Glycine max; biologický transport; kyseliny indoloctové; Indoleacetic Acids; Root Nodules, Plant; Plant Proteins; Biological Transport; kořenové hlízky rostlin; rostlinné proteiny